Comparative Study of Prestress Losses - Boukendakdji, M.; Touahmia, M.; Achour, M. (Engineering, Technology & Applied Science Research, 2017)
This paper compares the prestress losses as calculated by four different design codes; British standard CP110, Comite Europeen du Beton 70 and 78, American Concrete Institute 77 and the Prestressed Concrete Institute method (PCI). The comparison is done by determining the total losses which take place in a rectangular prestressed concrete beam for both pre-tensioning and post-tensioning systems. The results show that total losses calculated for the post-tensioning method are higher than those calculated for the pre-tensioning method, which is not the usual case. It seems that the PCI method may be required for special structures or for simply supported slender members which may be sensitive to small changes in deflections. However, for non-special structures, or where actual losses have little effect on the design, it is better to compute losses by the ACI method because it is simple and does take into considerations interactions between the various sources of losses. However, it is not possible to conclude which method gives the more accurate prediction of shrinkage and creep without direct co-relation to realistic insitu data.